AB0638 Risk Factors and Onset of Renal Involvement in Children with Schoenlein Henoch Purpura. (9th June 2015) - De Vivo, D.; La Mazza, A.; Fede, C.; Vitale, A.; Ventrici, C.; Conti, G.; Fede, C.
Abstract : Background: Henoch-Schöenlein purpura (HSP) is the most common vasculitis in children, characterized by multisystem involvement. Renal complication occurs in 30-40% of HSP children. It is the most serious complication in the chronic outcome. Objectives: Objective of the study is to evaluate the possible risk factors of renal complications in our series of children with HSP. Moreover we have tried to determine the time of onset of renal involvement. Methods: Retrospective study was conducted in children with HSP in our Department with follow-up of at least 24 months. We evaluated 66 children, 37 males and 29 females. We have considered as risk factors of renal complication the sex, the presence or history of allergy, the joint and intestinal involvement. Results: 20/66 HSP children have showed renal involvement (RHSP). RHSP was more frequent in males (14/20: 70%) versus females (6/20: 30%). Among the 46 children without renal involvement 24 (52%) were male and 22 (48%) females. Our data show that the male has greater risk of developing renal complications (OR 2.13; 95% CI 0.69 to 6.54).Average age of onset of vasculitis is 75.5±24 months in the RHSP versus 72.1±33.6 months in HSP without renal involvement. There was no difference in joint (60% versus 63%) and/or bowel (50% versus 41%) involvement between the two groups. Allergic symptoms occurred in 15% of RHSP children versus 29% of HSP children without renal involvement. Renal involvement developed in 30% of cases at onset of HSP; in 60% within 10 days of the diagnosis, and in 90% within 6 months. Only two children had renal complication after 12 and 18 months from diagnosis. Six renal biopsies were performed: 3 at the onset of illness and 3 within ten days from HSP diagnosis. Cutaneous recurrences occurred more frequently in the HSP group without renal involvement (30%) than in RHSP (5%) (OR 8.3; 95% CI 1.01 to 68.33). Conclusions: Our data showed that the male is the greater risk factor for renal complications in HSP patients. The renal involvement occurred mostly at onset and in the majority of cases within 6 months. In addition, the renal complication is more severe in the early days of onset of HSP as evidenced by the greater frequency of renal biopsies. We recommended to monitor carefully urine exam in the first 6 months from onset of vasculitis. Cutaneous relapses were rare in patients with RHSP, indicating a different pathogenetic mechanism and phenotypic expression between HSP patients. References: Narchi H. Risk of long term renal impairment and duration of follow up recommended for Henoch-Schonlein purpura with normal or minimal urinary findings: a systematic review. Arch Dis Child 2005;90:916–920. Disclosure of Interest: None declared